Real-time motion planning for quadcopter using adaptive spherical expansion and sequential convex optimization - Karaman, Atakan; Kurt, Huseyin Burak; Millidere, Murat; Alam, Mushfiqul (American Institute of Aeronautics and Astronautics (AIAA), 2023)
This paper introduces the Adaptive Spherical Expansion and Sequential Convex Programming (ASE-SCP) as a real-time motion planning algorithm. ASE-SCP algorithm is an improved version of the Spherical Expansion and Sequential Convex Programming (SE-SCP) algorithm in terms of computational speed. ASE-SCP is a hybrid real-time motion planning algorithm which combines the advantages of the Adaptive Spherical Expansion, such as approaching the neighborhood of the global optimal path, and the quick convergence ability of the Sequential Convex Programming. The ASE-SCP algorithm first finds a collision-free path using the adaptive spherical expansion approach. After finding a feasible path from the start point to the target point, the feasible path is re-optimized (tuned) using sequential convex optimization to find the suboptimal path. ASE-SCP Algorithm is applied to a quadcopter model to demonstrate its applicability.